Efficacy of compression and phlebotropic therapy varicose veins in pregnant women - V. Ya. Khryshchanovich; N. A. Rogovoy; N. Ya. Skobeleva; O. V. Krasko (Амбулаторная хирургия, 2023)
Introduction. Pregnancy is the leading cause of varicose veins(VVs) in women. Therapeutic measures during pregnancy include the wearing of compression hosiery and the phlebotropic therapy.Purpose. To evaluate the clinical effectiveness of graduated elastic compression and phlebotropic therapy in pregnant women with VVs.Materials and methods. A total of 88 pregnant women were included, 30 of whom used compression stockings (group 1), 28 women received phlebotonics together with compression (group 2) and 30 were controls. VVs severity was determined using the Venous Clinical Severity Score (VCSS). Quality of life (QoL) was calculated using the Chronic Venous Insufficiency Questionnaire (CIVIQ-20). The calf circumference was measured with a measuring tape in an orthostatic position.Results and discussion. At the end of the study there was a decrease in VCSS (p < 0.001 and p < 0.008) in both treatment groups, whereas the control group showed an increase in VCSS severity (p < 0.001). At the end of follow-up the QOL score in the treatment groups showed a tendency to improve while the control group showed a decrease in QOL. A bilateral decrease in tibial circumference (p < 0.001) was seen in groups 1 and 2 and the adjuvant phlebotropic treatment was found to be superior in controlling the oedema.Conclusions. The combined use of elastic compression and phlebotonics is more effective in eliminating venous oedema in pregnant women with VVs.